Copper, Zinc, and Selenium Levels During Pregnancy and Their Relationship with Pre-Eclampsia Risk: A Systematic Review - Goularte, Pietra dos Santos; Imperador, Carlos Henrique Lima; Piedade, Felipe Hassan; Guerin, Amanda Nascimento; Martins, Karina de Toledo; Boreski, Diogo [UNESP]; Gabriel, Edmo Atique; Gabriel, Sthefano Atique; Tiezzi, Daniel Guimarães; Chin, Chung Man [UNESP] (MDPI, 2025)
Pre-eclampsia (PE) affects about 5% of all pregnancies worldwide and is one of the leading causes of maternal and fetal morbidity and mortality. Some reports suggest that micronutrients may influence this condition, but there is no existing report analyzing data on copper (Cu), selenium (Se), and zinc (Zn) regarding quality and bias. Accurate information is crucial to support governmental healthcare actions, especially in developing countries such as Brazil. This study aims to investigate whether alterations in Zn, Cu, and Se levels in pregnant women contribute to the development of PE. We conducted the study following PRISMA guidelines and registered it on PROSPERO (CRD42022302298). We searched LILACS, PubMed/MEDLINE, EMBASE, and the Cochrane Library databases from January 2000 to January 2024. Of 1202 reports, 42 manuscripts were suitable for analysis (contained one or more micronutrients). A total of 76 individual analyses (by nutrient) were performed using Joanna Briggs Critical Appraisal and Cochrane Risk of Bias Tools. The analyses classified 69 reports as fair/low-quality with bias. Due to this, a meta-analysis was not conducted, as the results would not have accurately reflected reality. Of the high-quality reports, five on Cu showed conflicting results, while two studies on Zn found no differences in the level of this micronutrient between normal and PE pregnancies. No high-quality studies were identified for Se. The results highlight the need for robust guidelines for research involving micronutrients and PE to address this question effectively.
Keywords: copper; micronutrient; pre-eclampsia; pregnant; selenium; zinc